2012
DOI: 10.1017/s0954579411000642
|View full text |Cite
|
Sign up to set email alerts
|

Postadoption parenting and socioemotional development in postinstitutionalized children

Abstract: Children adopted from institutions (e.g., orphanages) overseas are at increased risk of disturbances in social relationships and social understanding. Not all postinstitutionalized children exhibit these problems, although factors like the severity of deprivation and duration of deprivation increase their risk. To date, few studies have examined whether postadoption parenting might moderate the impact of early adverse care. Three groups were studied: postinstitutionalized and foster care children both adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 66 publications
1
67
2
3
Order By: Relevance
“…The researchers found no differences between adoptive mothers’ parenting in infancy, compared with previously published normative samples, but found that adoptive mothers demonstrated less sensitivity/responsiveness than a group of non-adoptive mothers when adopted children and matched comparison children were 7 years old. A later study examined emotional availability in parents of children adopted from institutions compared with parents of children adopted early from foster care and parents of non-adopted children (Garvin et al, 2012). They found that when observed on average six months after adoption, when children were 18 months old, parents of PI children were more intrusive and provided poorer structure than socioeconomically similar non-adopting parents.…”
Section: Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found no differences between adoptive mothers’ parenting in infancy, compared with previously published normative samples, but found that adoptive mothers demonstrated less sensitivity/responsiveness than a group of non-adoptive mothers when adopted children and matched comparison children were 7 years old. A later study examined emotional availability in parents of children adopted from institutions compared with parents of children adopted early from foster care and parents of non-adopted children (Garvin et al, 2012). They found that when observed on average six months after adoption, when children were 18 months old, parents of PI children were more intrusive and provided poorer structure than socioeconomically similar non-adopting parents.…”
Section: Parentingmentioning
confidence: 99%
“…While it is clear that the adoptive parents offer care that is far better than the care received in the institutions, little research has measured the quality of this parenting compared to parenting of birth children among families of similar educations and incomes to these internationally adopting families. Further, despite this improvement in caregiving, there is still variation in the quality of post-adoption care children receive and little is known about which post-adoption factors contribute to recovery (Garvin, Tarullo, Van Ryzin, & Gunnar, 2012). Moreover, little is known about the bidirectional effects of parent and child characteristics in post-adoption families during this transitional phase that may facilitate changes in children’s behavior.…”
mentioning
confidence: 99%
“…In particular, maternal EA has been linked to child attachment security [4,5,6]. Moreover, longitudinal studies have shown that high EA predicts better emotion regulation [7], lower rates of psychopathological symptoms [6,8], higher social competence [9], better language skills and general mental development [10], and better theory of mind (ToM) skills in children [11]. Thus, several empirical findings underline the huge significance of high maternal EA for healthy child development.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Yehuda et al (5) and others (6,7) illuminated the systematic vulnerabilities sustained by children of the Holocaust and famine survivors, and research by Evans and Schamberg (8), Shonkoff and Phillips (9), Hackman and Farah (10), Neville and colleagues (11), Lupien et al (12), and Felitti et al (13) has systematically documented the neurodevelopmental and health consequences of rearing in conditions of poverty and adversity. Most recently, studies by Rutter (14), Gunnar and colleagues (15), Smyke et al (16) and Nelson et al (17) have described the socioemotional and cognitive deficits sustained by children growing up in orphanages and other institutional settings with nonparental care. Hertzman and Boyce (18) and Hertzman and coworkers (19) have geographically mapped such deficits, linking developmental vulnerabilities at primary school entry to the unique geosocietal circumstances of individual communities.…”
mentioning
confidence: 99%